Chemistry and Quantum Mechanics in 2019: Give Us Insight and Numbers - Neese, Frank; Atanasov, Mihail; Bistoni, Giovanni; Maganas, Dimitrios; Ye, Shengfa (Journal of the American Chemical Society, 2019)
This Perspective revisits Charles Coulson's famous statement from 1959 "give us insight not numbers" in which he pointed out that accurate computations and chemical understanding often do not go hand in hand. We argue that today, accurate wave function based first-principle calculations can be performed on large molecular systems, while tools are available to interpret the results of these calculations in chemical language. This leads us to modify Coulson's statement to "give us insight and numbers". Examples from organic, inorganic, organometallic and surface chemistry as well as molecular magnetism illustrate the points made.